Effect of replacing different levels of skimmed milk powder with fish-meal on nutrient utilization - SINGH, R N; SINGH, S K S; BHAKT, R; SRIVASTAVA, J P (The Indian Journal of Animal Sciences, 2014)
Piglets (136), each weaned fractionally at 5 kg weight, after 3 weeks of age, belonging to Landrace, Tamworth and their crosses with desi were taken for the present study. The control group (T1 ) was fed standard pre-starter diet (20% CP and 3500 Kcal DE/kg.of diet) containing 8% skimmed milk powder (SMP). Experimental groups T2 and T3 were fed diets in which 25 and 50% ofSMP was replaced by fish-meal, respectively, on isoproteinous and isocaloric basis. The average body weight at eighth week of age in T1 , T2 and T3 diets, did not differ significantly. There was no significant difference among diets with respect to nutrient utilization. The feed conversion efficiency in T1 , T2 and T3 groups were 2.17: 1,2.25: 1 and 2.32: 1, respectively. The cost offeed/kg gain in body weight were significantly higher in TT1 (Rs 13.36) than that in T2 (Rs 12.50) and T3 (Rs 12.38), the difference between later 2 diets was nonsignificant. It was thus concluded that 50% of the SMP can economically be replaced by fish-meal without affecting the palatability and nutritive values of the prestarter diets besides growth rate of piglets.